Al-Qur'ān Interpretation Pattern by Adi Hidayat on Adi Hidayat Official YouTube Channel - M. Suryadinata; Abdul Wahid; Ernawati Ernawati; Juhrah M. Arib; Sudarmadi Putra (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to analyze Adi Hidayat's al-Qur'ān interpretation on an official YouTube channel. It ensures that the public is not exposed to inferior information as the use of new media to interpret the al-Qur'ān in the digital age increases and regulation becomes more complex. Therefore, new problems in the al-Qur'ān interpretation are inevitable. Becoming a mufassīr necessitates expertise, and the al-Qur'ān interpretation should adhere to the same rules. A qualitative and virtual ethnographic approach was used to analyze the data. Primary data was obtained from Adi Hidayat's video interpretation of sūrah an-Nūr, sūrah Yusūf, and tafsīr on the Jewish genealogy history, as well as studies on Islamic questions and answers. Similarly, books and journals were used as secondary data and analyzed using qualitative analysis techniques. The results showed that Adi Hidayat's interpretation style was lugāwī and tended to use the mauḍū'i than the tahlīlī method with the bil ma'sūr and bil ra'yi approaches. Additionally, the tafsīr book was not the only source of interpretation and tends to rely on personal ijtihād through language analysis, as well as reviewing the wisdom of a verse rather than explaining the global meaning. This study contributes to the discovery of the al-Qur'ān interpretation aspects by Adi Hidayat. It shows the importance of social media as an essential tool for mufassīr because of its easy accessibility for the public.